Stability and accuracy of numerical boundary conditions in aeroelastic analysis - Giles, M (1997)
This paper analyses the accuracy and numerical stability of coupling procedures in aeroelastic modelling. A two-dimensional model problem assuming unsteady inviscid flow past an oscillating wall leads to an even simpler one-dimensional model problem. Analysis of different numerical algorithms shows that in general the coupling procedures are numerically stable, but care is required to achieve accuracy when using very few time steps per period of natural oscillation of the structure. The relevance of the analysis to fully three-dimensional applications is discussed. © 1997 by John Wiley and Sons, Ltd.